Serum Lipid Profile and Inflammatory Severity in Acne Vulgaris: Implications for Metabolic Health - Kapantow, Marlyn Grace; Kapantow, Nova Hellen; Kairupan, Tara Sefanya; Gaghana, Sthefanie Mariska; Christopher, Paulus Mario (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Acne vulgaris (AV) is a chronic inflammatory disorder of the pilosebaceous unit with varying degrees of severity. Increasing evidence suggests that metabolic disturbances, including dsylipidemia, may contribute to its inflammatory progression. This study aimed to investigate the association between serum lipid profiles and AV severity. Methods: A cross-sectional study was conducted among 30 patients with AV aged 25–40 years at a tertiary hospital in Manado, Indonesia. Serum triglycerides, low-density lipoprotein (LDL), high-density lipoprotein (HDL), and total cholesterol levels were measured. Association between lipid parameters and AV severity were assessed using Spearman’s rank correlation. Group differences were analyzed using one-way ANOVA or the Kruskal-Wallis test with post-hoc analysis.Results: Participants were predominantly Minahasa (66.7%) and female (60.0%). Total cholesterol and LDL levels demonstrated strong positive correlations with AV severity (r=0.696 and 0.654, respectively; p<0.001). Patients with severe AV had significantly higher total cholesterol and LDL levels compared to those with mild and moderate AV (F= 13.275; p<0.001 for total cholesterol; H= 12.496; p=0.002 for LDL). Triglycerides levels showed a weak correlation with AV severity (r= 0.375; p=0.041) but no significant intergroup difference (p= 0.112). HDL levels were not significantly associated with AV severity (p= 0.198).Conclusions: Dyslipidemia, specifically elevated total cholesterol and LDL, is strongly associated with severe AV. These findings underscore the importance of metabolic evaluation and lifestyle-based interventions as part of comprehensive management to reduce inflammation and promote long-term metabolic health.